Modeling language, cognition and action :proceedings of the ninth Neural Computation and Psychology Workshop, University of Plymouth, UK, 8-10 September 2004 /, Guido Bugmann, Roman Borisyuk. - Cangelosi, Angelo
Includes bibliographical references and index.